Open source systems: grounding research 7th IFIP WG 2.13 International Conference, OSS 2011, Salvador, Brazil, October 6-7, 2011. Proceedings - Hissam, Scott (IFIP Advances in Information and Communication Technology, 2011)
This book constitutes the refereed proceedings of the 7th International IFIP WG 2.13 Conference on Open Source Systems, OSS 2010, held in Salvador, Brazil, in October 2011. The 20 revised full papers presented together with 4 industrial full papers, 8 lightning talks and 2 workshop papers were carefully reviewed and selected from 56 submissions. The papers are organized in the following topical sections: OSS quality and reliability, OSS products, review of technologies of and for OSS, knowledge and research building in OSS, OSS reuse, integration, and compliance, OSS value and economics, OSS adoption in industry, and mining OSS repositories.